Redox and catalytic properties of RhxCe1−xO2−δ solid solution - Kibis, Lidiya S.; Kardash, Tatyana Yu; Derevyannikova, Elizaveta A.; Stonkus, Olga A.; Slavinskaya, Elena M.; Svetlichnyi, Valerii A.; Boronin, Andrei I. (The Journal of Physical Chemistry C)
In this work, a detailed study of the redox properties of solid solution RhxCe1-xO2-δ in correlation with its catalytic activity in CO oxidation reaction was carried out. The ex situ X-ray photoelectron spectroscopy technique was applied to follow the charging states of the elements on the surface during the redox treatments at a temperature range of 25-450 °C. The results were compared with the data of temperature-programmed reduction by CO. The dissolution of rhodium in the ceria bulk considerably increased the mobility of CeO2 lattice oxygen, with redox transitions Ce4+ ↔ Ce3+ and Rh3+ ↔ Rhn δ+ observed already at low temperatures (below 150 °C). The reduced rhodium clusters (Rhn δ+) formed during the reduction treatment significantly improved the catalytic activity of the RhxCe1-xO2-δ solid solution. The small size of the rhodium clusters (Rhn δ+) and high defectiveness of the fluorite phase provided the reversibility of Rhn δ+/CeO2 ↔ RhxCe1-xO2-δ transitions upon redox treatment, resulting in the high reproducibility of the CO conversion curves in the temperature-programmed reaction CO + O2. The homogeneous solid solution was stable up to 800 °C. Above this temperature, the CeO2 volume was depleted of Rh3+ ions because of their partial segregation into the surface and/or subsurface layers with the formation of Rh2O3. For these inhomogeneous samples, the oxygen mobility was considerably lower, while the redox transitions, Ce4+ ↔ Ce3+ and Rh3+ ↔ Rhn δ+, required higher temperatures. © 2017 American Chemical Society.